Thinking through tourism
1 online resource.
Keywords: The study of tourism has made key contributions to the study of anthropology. This volume defines the current state of the anthropology of tourism, examining political, economic, ideological and symbolic themes. An extraordinarily rich collection of case studies illustrate topics as diverse as hospitality, sex and tourism, enchantment, colonial and neo-colonial consumption, and the relation between tourism and gender and ethnic boundaries, as well as questions of global, economic and cultural systems, modernism and nationalism. The book also covers practical and policy issues relating to urban, rural and coastal planning and development. Thinking through Tourism assesses the enormous potential contribution that analysis of tourism can offer to mainstream anthropological thinking. The volume opens up new avenues for enquiry and is an essential resource for students and scholars of anthropology, geography, tourism, sociology and related disciplines.